A Proposed Pandemic Clause for Force Majeure Events under Construction Contracts in Malaysia. (2021) - Zin, Shahrizal Mohd; Rahmat, Nur Ezan; Razak, Abdul Mu'iz Abdul; Fathi, Nik Hasbi; Budiartha, I Nyoman Putu
No abstract available